Minority Salience and Criminal Justice Decisions - Kyra Hanemaaijer; Nadine Ketel; Olivier Marie (Institute of Labor Economics (IZA), 2024)
When decision-makers overemphasize salient features under limited attention, biased decisions can result in settings in which decisions should be unbiased. We exploit a sudden shock in the salience of individuals of Moroccan descent in the Netherlands to test the vulnerability of decisions of various actors in the Dutch criminal justice system to biases. Using high-quality data on decisions made from arrest through appeal in the Dutch CJS, we find that the sentence length of individuals of Moroccan descent convicted of a crime increased by 79% after the shock. Heterogeneity analyses indicate that more-experienced judges mitigate this effect. Finally, we find suggestive evidence of longer-term costs for defendants of Moroccan descent in that their labor income drops by 40% over the four years following their judgment of conviction.
Keywords: J15; K42; D83; 330; salience; minority; criminal justice system; Netherlands